Assessment of Physical Activity Level and Its Effects on Blood Pressure Control among Hypertensive Patients Attending Kiambu Level Five Hospital, Kenya - Mbijiwe, Jane; Chege, Peter; Munyaka, Anne (International Journal of Health Sciences & Research, 2019)
Hypertension is a global public health concern since it contributes to onset of heart related diseases. Control of blood pressure among hypertensive patients is important to reduce cardiovascular disease events. Lifestyle modifications that involve engagement in exercise and physical activity are some of the measures that have been found to be appropriate in maintenance of optimal blood pressure levels among hypertensive patients. There exists paucity of information on physical activity level of hypertensive patients. The objective of this study was therefore to determine the physical activity level of hypertensive patients in Kenya. The study engaged 134 hypertensive adult patients attending Kiambu Level Five Hospital. A structured questionnaire was used to collect data on demographic characteristics and physical activity level. Data analysis was done using statistical package for the social science. The relationship between blood pressure level and physical activity was determined by use of Pearson correlation test. A p-value of <0.05 was used as criterion for statistical significance. The current study found that hypertensive patients had low levels of physical activity (63.0%). Physical activity was found to be negatively correlated to blood pressure meaning that; as physical activity increased blood pressure level decreased (r=-0.211, p=0.012). Subsequently, health professionals should encourage hypertensive patients to engage in physical activity with special attention being drawn on the influence of physical activity to blood pressure level. This could be done by organizing health talks informing the patients of the benefits physical activity would have on their health.
Keywords: Hypertension; blood pressure; Physical activity